Descriptive Analysis of the Implementation AISAS Model and Digitalization of Accounting in the Cisaat Tourism Village - Afghani Mahmuda Bahreisy; Gita Siswhara; Asep Kurniawan (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2026)
This study aims to analyze consumer behavior in Cisaat Tourism Village through the development of the AISAS model (Awareness, Interest, Search, Action, Share) and the implementation of digital accounting. The method used is a qualitative descriptive approach with a case study, involving in-depth interviews, participatory observation, and document analysis. Cisaat Tourism Village, located in Ciater Subdistrict, Subang Regency, West Java Province, is renowned as an Educational Tourism Village. In 2024, it received an award from the Ministry of Tourism and Creative Economy as the third-ranked Emerging Tourism Village. The study results show that the majority of tourists became aware of Cisaat Tourism Village through Instagram, TikTok, and travel agents. They became interested in visiting the village due to its engaging videos. Subsequently, they searched for information on Google Search, TikTok, Instagram, and YouTube. Next, they took action by enjoying the unique beauty, hospitality, and educational experiences offered by Cisaat Tourism Village. Finally, tourists often shared their travel experiences through WhatsApp stories, Instagram, and TikTok. However, the use of digital accounting technology has not yet been implemented in Cisaat Tourism Village.